2011
DOI: 10.2478/s11756-011-0073-7
|View full text |Cite
|
Sign up to set email alerts
|

The flight distances of floodwater mosquitoes (Aedes vexans, Ochlerotatus sticticus and Ochlerotatus caspius) in Osijek, Eastern Croatia

Abstract: Abstract:In spring 2004, the mark-release-recapture study was conducted in the Osijek area, covering the total of 171 km 2 , to describe dispersal pattern of three floodwater mosquito species (Aedes vexans, Ochlerotatus sticticus and Oc. caspius). Forty CO2 baited Center for Disease Control and Prevention (CDC) traps were set at distances varying from 0.95 to 16.7 km from release site. Fifty thousand mosquitoes were released, and a total of 22 marked mosquitoes were recaptured in 12 traps, 82% of which were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…As the availability of water is an important driver of mosquito population dynamics, both mosquito abundance and RVF suitability were expected to be higher in the vicinity of permanent rivers and lakes. Active dispersal distance is short for most mosquito species (<1 km) (Harrington et al., ; Yamar et al., ; Krida et al., ), but other studies conducted in temperate regions on potential RVFv species (listed below) report larger distances (Brust, ; Bogojević et al., ). Therefore, we considered a linear decreasing relationship between both enzootic and epizootic suitability for RVF and distances from permanent water sources (with maximum and minimum thresholds at 0 and 10 km, respectively) (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…As the availability of water is an important driver of mosquito population dynamics, both mosquito abundance and RVF suitability were expected to be higher in the vicinity of permanent rivers and lakes. Active dispersal distance is short for most mosquito species (<1 km) (Harrington et al., ; Yamar et al., ; Krida et al., ), but other studies conducted in temperate regions on potential RVFv species (listed below) report larger distances (Brust, ; Bogojević et al., ). Therefore, we considered a linear decreasing relationship between both enzootic and epizootic suitability for RVF and distances from permanent water sources (with maximum and minimum thresholds at 0 and 10 km, respectively) (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…In other testing of Mosquito Magnets over the past 5 years, Culex Environmental has found that the placement of these traps is a key factor in maximizing catches. Dispersal patterns of emerging adult mosquitoes vary between species (Bogojević et al 2010), and adults are rarely evenly distributed across the landscape, often following prevailing winds for distances upwards of 10 km after emergence (Brust 1980). Many mechanical devices, including Mosquito Magnets, have the added capacity of utilizing octenol (1-octen-3-ol) as an attractant, which has been found to improve trapping success in many studies (Kline 2006, Qualls and Mullen 2007, Li et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a distance of 3500 m was assumed, because the Aedes and Anopheles mosquitoes have an average MFD of 3500 m (Verdonschot & Besse-lototskaya, 2014). Areas located closer than 3.5 km from the mosquito breeding pools were considered as high hazard zones; however, some studies report that under some circumstances, mosquitos may fly up to 10 km (Bogojevic, Merdic, & Bogdanovic, 2011). Thus, areas located closer than 10 km from the mosquito breeding pools were considered as low hazard zones.…”
Section: Flood Duration Hazardmentioning
confidence: 98%